1991
DOI: 10.1177/001872089103300106
|View full text |Cite
|
Sign up to set email alerts
|

Eyestrain in VDU Users: Viewing Distance and the Resting Position of Ocular Muscles

Abstract: Without fixation stimuli--for instance, in darkness--accommodation and convergence of the eyes reach an intermediate state that is relatively stable within a subject but which ranges from about 30 cm to infinity across subjects. This study investigated whether these oculomotor positions in darkness are related to visual strain. During work at a visual display unit (VDU), visual strain at a viewing distance of 50 cm was stronger than at 100 cm (with characters twice as large). The more distant the individual's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 21 publications
6
78
0
1
Order By: Relevance
“…This finding was consistent with Shieh and Lin's study [10], which suggested that maintaining a brighter ambient illumination level (about 450 lux), rather than reducing it to a lower level (200 lux). Based on our experimental settings, the luminance contrast ratio (L background /L text ) of the projected text was controlled at 3:1.…”
Section: Ambient Illumination Effect On Film-watching Performancesupporting
confidence: 91%
See 1 more Smart Citation
“…This finding was consistent with Shieh and Lin's study [10], which suggested that maintaining a brighter ambient illumination level (about 450 lux), rather than reducing it to a lower level (200 lux). Based on our experimental settings, the luminance contrast ratio (L background /L text ) of the projected text was controlled at 3:1.…”
Section: Ambient Illumination Effect On Film-watching Performancesupporting
confidence: 91%
“…The issue of visual fatigue at a computer workstation has been noted in the previous studies [8][9][10][11]. Some VDT tasks can cause symptoms of fatigue and some can result in temporary reduction of visual ability.…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor for eye discomfort was short distances between the eyes and the VDT, consistent with the findings of some studies (33,34) that suggeste d an increase in fatigue with short distances, especially in individuals with a disparity betwee n the (shorter) viewing distance and the individual's (longer) dark convergence. For dryness, there was an apparent interaction in our study between large variations in the distance to the eye task objects and the use of monofocal glasses during VDT work.…”
supporting
confidence: 87%
“…Therefore, this should be possible without adopting extreme postures. However, it is preferable that mammographers use the digital magnification tool, as using external magnification will not change the finite pixel size of the VDU screen, and moving the head close to the VDU screen has been associated with eye strain 15,16 . Therefore, magnification tools should be simple and intuitive to operate, and as similar to the known activity of using a magnifying glass as possible.…”
Section: Discussionmentioning
confidence: 99%